2021
DOI: 10.2196/16490
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone-Based Interventions and Internalizing Disorders in Youth: Systematic Review and Meta-analysis

Abstract: Background Mental health disorders in youth are a global issue that have important implications for the future quality of life and morbidity of affected individuals. In the context of public health initiatives, smartphone-based interventions have been suggested to hold the potential to be an effective strategy to reduce the symptoms of mental health disorders in youth; however, further evaluation is needed to confirm their effectiveness. This systematic review and meta-analysis documents and synth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
3
17
0
Order By: Relevance
“…The study indicated high-risk addictions, resulting in low self-regulated smartphones. Similarly, Buttazzoni et al (2021) concur with this research that smartphones spend most users' time and don't.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The study indicated high-risk addictions, resulting in low self-regulated smartphones. Similarly, Buttazzoni et al (2021) concur with this research that smartphones spend most users' time and don't.…”
Section: Discussionsupporting
confidence: 84%
“…The smartphone usage of students is both negatively and beneficial depends on how it is utilised, according to Buttazzoni et al (2021). The author further stresses that the smartphone has become a big distraction from studying on the wrong sides of the coin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reviews investigating the effectiveness of app-based mental health interventions found a similar trend. 70 This potentially reflects the fact that app-based interventions are still in the nascent stages. More rigorous designs of apps for youth mental health are needed.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review found only 12 studies that evaluated smartphone-based interventions for internalising disorders in adolescents. Only three of these interventions were based on CBT and none were apps for depression or anxiety disorders or symptoms (Buttazzoni et al, 2021). Smartphones provide unceasing access to software, internet and multimedia functionality.…”
Section: Introductionmentioning
confidence: 99%